The crisis in Ukraine and Russia’s global strategy - A. O. Bezrukov (Ибероамериканские тетради, 2023)
When studying the conflict unfolding in Ukraine, two axes of confrontation are most often considered: Russia versus Ukraine and Russia versus the West. The author is convinced that such division is a false dyad. Ukraine is a kind of battering ram, which has been prepared with regard to the specific class organization, as well as militarily. Through Ukraine, the West is trying to solve its main foreign policy objective, i.e. to eliminate Russia as an adversary and then, before the momentum is lost, to challenge China as well. Nevertheless, the West is weakening and is in a phase where it is starting to lose its global position. Thus, for the West, which is coming to realize that it is on the verge of a political and economic crisis, the war in Ukraine is the last chance to deal with two key issues: to finish off its main adversaries by military and political means and at the same time, indirectly, to avoid a possible war.